Assessment of Qatar community pharmacists' competence and practices related to renal and gastrointestinal adverse effects of nonprescription NSAIDs - Yaw Boahene Owusu; Wishah Hamza Elkhalifa; Ahmed Awaisu; Nadir Kheir (Elsevier, 2022)
Introduction: Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most frequently dispensed nonprescription drugs in community pharmacies. However, inappropriate use of NSAIDs by consumers has been associated with development of gastrointestinal (GI) injuries and renal injuries. Community pharmacists' education of consumers on proper use of NSAIDs and their associated adverse effects has been shown to reduce the GI and renal injuries. In Qatar, no studies have been done to assess the community pharmacists' knowledge, attitude, and practices related to renal and GI adverse effects of NSAIDs. Therefore, this study aimed to assess Qatar community pharmacists' knowledge, attitude, and practices on the safe use of nonprescription NSAIDs to reduce the risk of kidney and GI injuries. Methods: A cross-sectional web-based survey was conducted among community pharmacists in Qatar. A pre-tested 28-item questionnaire that was developed through a multi-phase iterative process was administered to a convenient sample of community pharmacists in Qatar. Data were analyzed using descriptive and inferential statistics with statistical significance set at p < 0.05. Results: Overall, 114 community pharmacists responded to the online questionnaire (response rate 15.2%). Approximately 90% of the community pharmacists demonstrated from good to excellent knowledge on the renal and GI adverse effects of NSAIDs, with none of their sociodemographic and professional characteristics having a significant effect on their knowledge scores. More than half of the pharmacists reported that they always or usually educated patients on the dosage (98.6%), administration (95.8%), side effects and precautions (78%), and contraindications (71.2%) of NSAIDs during their routine practices. The majority of the pharmacists had positive attitude towards educating patients about adverse effects of NSAIDs, as well as identifying high-risk patients who should avoid nonprescription NSAIDs. However, 45.7% of the pharmacists strongly agreed or agreed that educating patients about NSAIDs can be time consuming. Conclusion: Community pharmacists in Qatar demonstrated good knowledge of the renal and GI adverse effects of NSAIDs with some obvious areas of improvement, and this can be reinforced through continuing professional development. They also showed positive attitudes towards protecting patients against the renal and GI adverse effects of NSAID. However, a significant proportion of the pharmacists admitted that educating patients on NSAIDs was time consuming, which is a cause of concern warranting further investigation. Community pharmacy managers should provide community pharmacists adequate time and support to educate individuals at risk of renal and GI injuries who obtain NSAIDs from their pharmacies. Also, the Ministry of Public Health of Qatar should consider making counseling on high-risk medications (e.g., NSAIDs and insulin) by community pharmacists mandatory so that measures can be put in place in the pharmacies to free the pharmacist for education and counseling.